Rapid, accurate and simple detection method for oxygen content in copper material and application of rapid, accurate and simple detection method
By combining micropolarization technology and metallographic analysis detection methods, the existing copper oxygen content measurement methods are solved, and the rapid, accurate and simple detection of the oxygen content in copper is achieved, and the production and application effect of copper materials is improved.
Patent Information
- Application Number
- CN202411935889.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-26
- Publication Date
- 2025-04-04
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The existing methods for measuring oxygen content in copper have high cost, low efficiency and low accuracy.
The detection method combined with micropolarization technology and metallographic analysis is used to observe the microstructure of the sample under a metallographic microscope after electrolytic polishing. The presence or absence of oxygen elements is analyzed using polarization characteristics, and the multiphase statistics and oxygen content are calculated through metallographic analysis software.
It realizes rapid, accurate and simple detection of oxygen content in copper materials. It is suitable for a variety of copper materials, which helps copper material production and quality control, ensures product quality and improves material performance.
Smart Images

Figure CN119757233A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of material detection and analysis, and specifically relates to a rapid, accurate and simple detection method for oxygen content in copper materials and an application thereof. Background Art
[0002] Copper is essential in many fields such as electronics, industry and aerospace, and its electrical conductivity, thermal conductivity and ductility are key. Oxygen content significantly affects the physical and chemical properties of copper, determining its life and reliability. Accurate determination of oxygen content helps control the production process, optimize material properties and enhance the application value of copper. Therefore, the development of high-precision oxygen content determination technology is of research value to improve the production and application of copper materials.
[0003] At present, the determination of oxygen content in copper mainly relies on direct measurement techniques such as chemical analysis, and indirect measurement methods such as hydrogen embrittlement test. The oxygen meter can directly measure the oxygen content, but the equipment has low accuracy and the instrument is expensive. The electrolytic titration method is easy to operate and the results are reliable, but it is limited by expensive electrochemical equipment. The hydrogen annealing method requires professional equipment and technology to determine the oxygen content, and the operation is complicated. The hydrogen relaxation method is accurate, but the process is complicated and the equipment is expensive. The infrared spectroscopy method is simple to operate, but it is easily interfered by other components. The oxygen content of oxygen-free copper is determined using the standard metallographic inspection method, which indirectly evaluates the oxygen content through hydrogen annealing technology, but there are problems such as insufficient accuracy and long operation time. In addition, the current laboratory does not have professional equipment for directly determining the oxygen content in copper, and lacks technical methods for indirectly determining the oxygen content in copper. Summary of the invention
[0004] The purpose of the present invention is to solve the technical problems of high cost, low efficiency and low accuracy of the existing method for determining the oxygen content in copper, and to provide a rapid, accurate and simple detection method and application of the oxygen content in copper.
[0005] One of the purposes of the present invention is to provide a method for quickly, accurately and simply detecting the oxygen content in a copper material, the method being carried out according to the following steps:
[0006] S1: On the basis of mechanically polished samples, electrolytic polishing is performed. The electrolyte consists of phosphoric acid, acetic acid, perchloric acid and ethanol. After polishing, cleaning and low-temperature drying are performed;
[0007] S2: Use a metallographic microscope to observe the sample in bright field mode at different magnifications. When sky blue fine-grained or round-grained phase structures appear on the surface, switch to polarization mode. If ruby-colored fine-grained or round-grained phase structures appear, it indicates that oxygen is present.
[0008] S3: Observe the sample under the condition of a metallographic microscope magnified to 200 times, mark the edge of the observed range, magnify the metallographic microscope to 500 times within the designated area to take pictures and use the image stitching function of the image processing software to stitch them together, and after stitching, reduce it to a sampling map of the image area size at a magnification of 200 times. Then, use the multi-phase statistics function of the metallographic analysis software to automatically process the sampling map, and obtain the area ratio of the cuprous oxide phase in the sampling map. Finally, calculate the oxygen content through the formula.
[0009] It is further defined that the volume content of each component in the electrolyte in S1 satisfies: phosphoric acid 5% to 10%, acetic acid 5% to 15%, perchloric acid 1% to 5%, and the balance is ethanol.
[0010] It is further specified that the volume content of each component in the electrolyte satisfies: phosphoric acid 5%, acetic acid 10%, perchloric acid 2%, and ethanol 83%.
[0011] Further defined, the electrolysis parameters in S1 are: voltage 15-40 V, electrolysis time 10-90 s, current density 0.1-1.0 A / cm 2 , electrolyte temperature <20℃.
[0012] It is further defined that the electrolytic polishing process in S1 is accompanied by stirring, and the rotation speed is 100 to 400 rpm.
[0013] It is further defined that the low temperature drying temperature in S1 is less than 35°C.
[0014] It is further defined that the electrolytic polishing in S1 uses a stainless steel plate, a metal platinum sheet or a graphite electrode as a cathode and pure copper as an anode.
[0015] Further defined, the different magnifications in S2 are 200X, 500X and 1000X.
[0016] Further defined, the formula described in S3 is as follows:
[0017] w o =0.39F 共晶 / / 100
[0018] Where: F 共晶 is the percentage (%) of the eutectic (i.e. cuprous oxide phase) occupying the viewing area under the microscope, w o is the oxygen content in copper (wt%).
[0019] A second object of the present invention is to provide an application of the above method in determining the oxygen content in copper materials.
[0020] The advantages of the present invention compared to the prior art are:
[0021] The present invention proposes a detection method combining microscopic polarization technology and metallographic analysis. The microscopic polarization inspection technology can more accurately determine the oxygen content and effectively judge the distribution of oxygen in the copper material. Although the method is not a direct measurement, it can analyze the microscopic characteristics of the sample through the characteristics of polarized light, judge whether the oxygen element exists, and use the metallographic analysis multiphase statistical software to quantitatively analyze the cuprous oxide phase, thereby calculating the oxygen content in the copper material. The combination of these two technologies enables the detection method to more comprehensively and accurately analyze the presence, distribution and content of cuprous oxide in the copper sample, thereby accurately calculating the oxygen content. The method is applicable to a variety of copper materials, which is helpful for the production and quality control of copper materials, ensuring product quality and improving material performance. Compared with the traditional microscopic polarization inspection method, the method of the present invention shows a better test effect in determining the oxygen content of pure copper with low oxygen content. Through high-magnification observation and statistical analysis, the microscopic details such as the grain size, precipitated phase distribution and organizational structure of the material can be more clearly revealed. The accuracy and credibility of the observation results are ensured, and the potential impact of deviation on the test results is effectively reduced. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] Figure 1 is the sampling diagram described in the embodiment of the present invention;
[0023] Figure 2 It is the sampling diagram described in Comparative Example 1;
[0024] Figure 3 This is the sampling diagram described in Comparative Example 2. DETAILED DESCRIPTION
[0025] The specific implementation steps of the method for rapid, accurate and simple detection of oxygen content in copper materials of the present invention are as follows:
[0026] Step 1: Sample preparation
[0027] (1) Sample cutting: Samples are taken from copper samples by wire cutting to ensure high accuracy. When sampling, water or oil is used to keep the sample cool. For strips with a thickness of ≤ 0.5 mm and small cross-section products such as strips and wires, the sample needs to be embedded and the test surface exposed. The effective test area is 50 mm 2 ~100mm 2 For thin or small products, sufficient samples must be taken to ensure that the sampling area is representative. If the size requirements are met, there is no need for mounting.
[0028] (2) Sample Mounting: Grind the sample and remove 0.1mm to 0.5mm of the surface layer, and cool it with water. Then, place the sample in a hard rubber or silicone mold using resin cold mounting technology, and fix the edges with materials of similar hardness. Mix epoxy resin and curing agent, pour into the mold, perform low vacuum cold mounting, and cure at room temperature.
[0029] (3) Sample grinding and mechanical polishing: The cleaned and dried samples need to be ground on silicon carbide sandpaper of different grits in sequence. After each change of sandpaper, the grinding direction is rotated 90°. First, use 360# or 400# silicon carbide sandpaper for rough grinding until the grinding marks are uniform. Then, use 800# to 2000# sandpaper for fine grinding until the grinding marks are consistent. First use mechanical polishing to roughly polish the ground samples on nylon, woolen cloth or fine canvas, using micron-grade aluminum oxide or diamond polishing paste. After washing and drying the samples, use nylon silk or silk materials for fine polishing, using finer diamond paste or aluminum oxide suspension to ensure that the surface is defect-free and smooth. Set the polishing machine to a speed of 500-1200rpm and polish for 5-10 minutes.
[0030] (4) Electrolytic polishing: Based on mechanical polishing, electrolytic polishing technology is used for further fine processing to eliminate the surface stress layer. The electrolyte is a mixed solution of phosphoric acid, acetic acid, perchloric acid and ethanol. The volume percentage of each component of the mixed solution is: 5% to 10% phosphoric acid, 5% to 15% acetic acid, 1% to 5% perchloric acid, and the balance is ethanol. In the electrolytic polishing process, stainless steel plates, metal platinum sheets or graphite electrodes are used as cathodes, and pure copper is used as anodes.
[0031] The voltage is 15-40V, the electrolysis time is 10-90s, and the current density is controlled at 0.1-1.0A / cm 2 During the electrolytic polishing process, the electrolyte temperature must be lower than 20°C, and the sample must be stirred with a stirrer at a speed of 100 to 400 rpm. Continuous stirring can evenly distribute the electrolytic polishing solution and effectively remove corrosion products on the copper surface. After electrolytic polishing, the sample is cleaned with clean water and anhydrous ethanol, and dried with an air gun or a non-heated hair dryer to keep the surface temperature below 35°C.
[0032] Step 2: Sample observation
[0033] First, the polished sample surface is placed under a metallographic microscope equipped with a linear polarization function for detailed observation. The magnification of the microscope is set to 200X, 500X, and 1000X to obtain detailed microstructural information. Repeated observations are performed at different magnifications in the bright field mode of the microscope. When sky-blue fine-grained or round-grained phase structures are found on the surface, it is necessary to switch to the polarization mode to further confirm the nature of this phase.
[0034] Secondly, when conducting polarization observation under a microscope, the polarizer and analyzer are in an orthogonal state to accurately observe the microstructure of the sample. During polarization observation, if the copper sample is found to contain ruby-colored fine-grained or round-grained phase structure, it indicates that the sample contains oxygen. Analyzing the composition and distribution of this phase in the sample provides key microscopic information for material research.
[0035] Step 3: Metallographic Analysis
[0036] The sample was observed under the condition of a metallographic microscope magnified to 200 times, and the edge of the observed range was marked. The metallographic microscope was magnified to 500 times within the demarcated area to take pictures and stitched using the image stitching function of the image processing software Image-Pro Plus. After stitching, it was reduced to a sampling diagram of the image area size at a magnification of 200 times in the standard method. The multi-phase statistics function of the metallographic analysis software ProImaging was then used to automatically process the sampling diagram to obtain the area ratio of the cuprous oxide phase in the sampling diagram. Finally, the oxygen content was calculated using the formula, which is as follows:
[0037] w o =0.39F 共晶 / / 100
[0038] Where: F 共晶 is the percentage (%) of the eutectic (i.e. cuprous oxide phase) occupying the viewing area under the microscope, w o is the oxygen content in copper (wt%).
[0039] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.
[0040] The experimental methods used in the following examples are conventional methods unless otherwise specified. The materials, reagents, methods and instruments used are conventional materials, reagents, methods and instruments in the art unless otherwise specified, and can be obtained through commercial channels by those skilled in the art.
[0041] Embodiment: The rapid, accurate and simple detection method of oxygen content in copper material of this embodiment comprises the following steps:
[0042] Step 1: Sample preparation
[0043] (1) Sample cutting: Samples are taken from pure copper samples by wire cutting. The sample size is 10mm*5mm*1mm, and the effective test area is 50mm 2 When sampling, use water to cool the sample and the blade. Use 400# silicon carbide sandpaper to grind the machining marks flat and remove 0.1mm of the surface layer.
[0044] (2) Sample mounting: After the sample is ground, cleaned and blown dry, it is placed in a silicone slice mold and fixed. Cold mounting king JCM1 resin powder and liquid curing agent (metallographic mounting material purchased from Hangzhou Jingjing Testing Instrument Co., Ltd.) are mixed evenly in a weight ratio of 12:9, poured into the mold, and vacuum cold mounting is performed using a low vacuum, and cured at room temperature.
[0045] (3) Sample grinding and mechanical polishing: The sample washed with water and blown dry needs to be ground on silicon carbide sandpaper of different particle sizes in sequence. After each change of sandpaper, the grinding direction is rotated 90°. First, use 400# silicon carbide sandpaper for coarse grinding until the wear marks are uniform. Then, use 800# to 2000# sandpaper for fine grinding until the wear marks are consistent. Using an automatic polishing device, the sample is placed on a fine canvas polishing disc with a micron-grade alumina polishing agent for coarse polishing. The speed is set to 1200rpm and the polishing time lasts for 5 minutes. Then, it is placed on a polishing disc covered with silk for fine polishing. Diamond polishing paste with a particle size of 0.25μm is selected. The surface reaches a mirror finish and is free of defects. After completion, rinse with water and blow dry.
[0046] (4) Electrolytic polishing: Based on mechanical polishing, electrolytic polishing technology is used for further fine processing to eliminate the surface stress layer. The electrolyte is a mixed solution of phosphoric acid, acetic acid, perchloric acid and anhydrous ethanol. The volume content of each component in the mixed solution is: 5% phosphoric acid, 10% acetic acid, 2% perchloric acid, and the balance is anhydrous ethanol. A metal platinum electrode is used as the cathode and pure copper as the anode. The electrolytic polishing voltage is 25V, the electrolysis time is 45s, and the current density is controlled at 0.3A / cm 2 , the electrolyte temperature is 15℃, the stirrer speed is 200rpm, stirring to make the electrolytic polishing liquid evenly distributed, and timely remove the corrosion products on the copper surface. After electrolytic polishing, wash with clean water and anhydrous ethanol in turn, and blow dry with a manual air gun. Keep the surface temperature below 35℃ during the drying process.
[0047] Step 2: Sample observation
[0048] First, the polished pure copper sample was placed under a metallographic microscope with linear polarization function and observed repeatedly at magnifications of 200 times, 500 times, and 1000 times.
[0049] In bright field mode, sky blue granular phase structure can be found at all three magnifications. At a high magnification of 1000 times, it is confirmed that the small particle phase is also sky blue particles. Then the polarization mode is switched to an orthogonal state between the polarizer and the analyzer to observe the microstructure of the sample.
[0050] In polarization observation, it was found that the phase was ruby red, indicating that the sample contained oxygen and was confirmed to be cuprous oxide phase. At the same time, the morphology, size and distribution characteristics of the oxide particles in the sample were observed.
[0051] Step 3: Metallographic Analysis
[0052] The sample was observed under the condition of 200 times magnification of the metallographic microscope, and the edge of the observed range was marked. The metallographic microscope was magnified to 500 times within the demarcated area (612μm*488μm) to take pictures and the image processing Image-Pro Plus image stitching function was used to stitch the obtained pictures. After stitching, the sample was reduced to the sampling diagram of the image area size at 200 times magnification in the standard method (see Figure 1 ). Then, the multiphase statistics function of the metallographic analysis software ProImaging was used to automatically process the sampling map, and the area ratio of the cuprous oxide phase in the sampling map was obtained. Finally, the oxygen content was calculated by the formula. The specific results are shown in Table 1.
[0053] Comparative Example 1:
[0054] The difference between this comparative example and the embodiment of the present invention is that: in step 3: a sampling map is prepared at 200 times the magnification using a standard method in the selected area (see Figure 2 ). Other steps and parameters are the same as those in the embodiment of the present invention.
[0055] Comparative Example 2:
[0056] The difference between this comparative example and the embodiment of the present invention is that step 1 (4) is omitted and the subsequent steps are directly carried out after mechanical polishing. At the same time, in step 3: a sampling map is prepared at 200 times the magnification using a standard method in the selected area (see Figure 3 ). Other steps and parameters are the same as those in the embodiment of the present invention.
[0057] When the oxygen element reaches the eutectic composition point in the copper material, all the oxygen will form a eutectic structure, and its content is exactly 0.39wt%. In this case, for the oxygen content (w O ) can be calculated using the following formula:
[0058] w o =0.39F 共晶 / / 100
[0059] Where: F 共晶 is the percentage (%) of the eutectic (i.e. cuprous oxide phase) occupying the viewing area under the microscope, w o is the oxygen content in copper (wt%).
[0060] By this method, the accurate value of oxygen content in the sample is obtained. The specific values are shown in Table 1.
[0061] Table 1 Statistical calculation results of pure copper metallographic analysis
[0062] Phase statistics calculation method Example Comparative Example 1 Comparative Example 2 <![CDATA[Cuprous oxide content F 共晶 (%)]]> 1.57 1.29 1.11 <![CDATA[Oxygen content w in copper o (wt%)]]> 0.0061 0.0050 0.0043
[0063] As a supplementary control, standard method image comparison analysis was performed. First, the oxide particle microstructure image was observed and recorded (see Figure 1 to Figure 3 ), and compared it with the standard image in detail, and the data results are shown in Table 2. Finally, the oxygen content in the pure copper material is evaluated. The oxygen content of the pure copper in the embodiment of the present invention is about 0.006%, and the evaluated values of the pure copper oxygen content in Comparative Examples 1 and 2 are between 0.004% and 0.006%.
[0064] Table 2 Standard results of pure copper metallographic analysis
[0065] Standard image comparison method Example Comparative Example 1 Comparative Example 2 <![CDATA[Oxygen content w in copper o (wt%)]]> 0.006 0.004~0.006 0.004~0.006
[0066] In summary, it can be seen that the oxygen content values obtained by different methods, the numerical values of the metallographic analysis multiphase statistical results and the numerical range of the image comparison are consistent. The oxygen content calculation and comparison values obtained by the method of the present invention are higher than those of the standard method comparative examples 1 and 2, which means that the metallographic images obtained by the standard method have certain deviations when measuring oxygen content. Compared with the standard method, the method of the present invention obtains the second phase image feature information with higher accuracy and resolution.
[0067] The above are only preferred specific embodiments of the present invention, which are all different implementations based on the overall concept of the present invention, and the protection scope of the present invention is not limited thereto. Any changes or substitutions that can be easily thought of by a person skilled in the art within the technical scope disclosed by the present invention should be included in the protection scope of the present invention. Therefore, the protection scope of the present invention should be based on the protection scope of the claims.
Claims
1. A rapid, accurate and simple method for detecting oxygen content in copper materials, characterized in that: The method: S1: On the basis of mechanically polished samples, electrolytic polishing is performed. The electrolyte consists of phosphoric acid, acetic acid, perchloric acid and ethanol. After polishing, cleaning and low-temperature drying are performed; S2: Use a metallographic microscope to observe the sample in bright field mode at different magnifications. When sky blue fine-grained or round-grained phase structures appear on the surface, switch to polarization mode. If ruby-colored fine-grained or round-grained phase structures appear, it indicates that oxygen is present. S3: Observe the sample under the condition of a metallographic microscope magnified to 200 times, mark the edge of the observed range, magnify the metallographic microscope to 500 times within the designated area to take pictures and use the image stitching function of the image processing software to stitch them together, and after stitching, reduce it to a sampling map of the image area size at a magnification of 200 times. Then, use the multi-phase statistics function of the metallographic analysis software to automatically process the sampling map, and obtain the area ratio of the cuprous oxide phase in the sampling map. Finally, calculate the oxygen content through the formula.
2. The method according to claim 1, characterized in that The volume contents of the components in the electrolyte in S1 satisfy the following requirements: 5-10% phosphoric acid, 5-15% acetic acid, 1-5% perchloric acid, and the balance being ethanol.
3. The method according to claim 2, characterized in that The volume content of each component in the electrolyte satisfies: phosphoric acid 5%, acetic acid 10%, perchloric acid 2%, and ethanol 83%.
4. The method according to claim 1, characterized in that: Electrolysis parameters in S1: voltage 15-40 V, electrolysis time 10-90 s, current density 0.1-1.0 A / cm 2 , electrolyte temperature <20℃.
5. The method according to claim 1, characterized in that The electropolishing process in S1 is accompanied by stirring, and the rotation speed is 100 to 400 rpm.
6. The method according to claim 1, characterized in that S1 medium and low temperature drying temperature is less than 35℃.
7. The method according to claim 1, characterized in that In S1, electrolytic polishing uses stainless steel plate, metal platinum sheet or graphite electrode as cathode and pure copper as anode.
8. The method according to claim 1, characterized in that: The different magnifications in S2 are 200X, 500X and 1000X.
9. The method according to claim 1, characterized in that: The formula described in S3 is as follows: <h2 style=";text-align:left;direction:ltr">w<h2 style=";text-align:left;direction:ltr"> o <h2 style=";text-align:left;direction:ltr"> =0.39F<h2 style=";text-align:left;direction:ltr"> 共晶 <h2 style=";text-align:left;direction:ltr"> / 100 Where: F 共晶 is the percentage of the cuprous oxide phase occupying the viewing area under the microscope, w o is the mass percentage of oxygen in copper.
10. Use of the method according to any one of claims 1 to 9 in determining the oxygen content in copper materials.
Citation Information
Patent Citations
Full-view-field quantitative statistical distribution representation method of precipitated phase particles in metal material
CN108226159A
Detecting method of tungsten-copper alloy granularity
CN110068525A
Aluminum alloy electropolishing solution and electropolishing solution method
CN110835778A
Full-field statistical & characterizing method of fluid micro-explored strain for alloy microstructure
US20190086194A1
Cited By
Combined detection method and system for oxygen content of oxygen-free copper
CN120992297A